Severe Murine Typhus Presenting with Acalculous Cholecystitis: A Case Report and Literature Review. (4th April 2017) - Spernovasilis, Nikolaos; Tsioutis, Constantinos; Zafeiri, Maria; Hamilos, Georgios; Gikas, Achilleas
Abstract : A 54-year-old otherwise healthy male, who was being evaluated for prolonged fever, developed clinical and ultrasonographic signs compatible with acute acalculous cholecystitis. Diagnosis of murine typhus was confirmed by serology and the patient was treated with doxycycline. He improved rapidly and all clinical and laboratory abnormalities returned to normal. The present case dictates that knowledge of the local epidemiology and keeping a high index of clinical suspicion can help recognize uncommon manifestations of murine typhus, in order to treat appropriately and avoid unnecessary investigations and interventions.